Approximation of the maximum frequency of operation for point‐contact MIM diodes from DC current against voltage measurements. Issue 7 (1st April 2015) - Snyder, G.; Rhoades, C.; Hagmann, M.J.
Abstract : Point‐contact metal–insulator–metal (MIM) diodes have been used for detection and mixing at frequencies as high as 520 THz. In detection, the current responsivity (CR), defined as the change in the DC current caused by an incremental change in the high‐frequency input power, depends on the dimensions of the diode and the test fixture. However, other researchers have shown that the intrinsic current responsivity (ICR) which sets an upper bound for the CR may be determined from DC current against voltage measurements. Additional calculations from DC measurements have been used to determine an upper bound for the maximum frequency of operation.